METODE ALTMAN Z-SCORE DAN SPRINGATE TERHADAP KINERJA KEUANGAN PERUSAHAAN TELEKOMUNIKASI BUMN DAN BUMS YANG TERDAFTAR DI BURSA EFEK INDONESIA - Balda, Fauziah; Pratomo, M Restu Aji; Sumarlin, Abdul; Abidin, Zainal (Sekolah Tinggi Ilmu Ekonomi Semarang, 2025)
Financial performance is a crucial indicator for assessing the sustainability and health of a company, particularly in the telecommunications industry, which faces high competition and substantial capital requirements. This study aims to analyze the influence of the Altman Z-Score and Springate methods in assessing the financial performance of state owned and privately-owned telecommunications companies listed on the Indonesia Stock Exchange, namely PT Telekomunikasi Indonesia Tbk and PT XL Axiata Tbk, for the 2021 2024 period. The research method used is quantitative with a descriptive and comparative approach. Secondary data were obtained from the companies' annual financial reports. The results indicate that the Altman Z-Score and Springate methods are capable of providing an overview of a company's financial health, although there are differences in the classification results between the two methods. PT Telekomunikasi Indonesia Tbk shows a relatively healthy financial condition, while PT XL Axiata Tbk is in the vulnerable or at-risk category for certain periods. These differences in results indicate that using more than one bankruptcy analysis method can provide a more comprehensive picture of a company's financial performance.